Letter from Daniel D.L. Farson to Margaret M. Booth, May 9, 1888 - Farson, Daniel D. L. (1888)
Pennsylvania Horticultural Society Secretary, Daniel D. L. Farson, writes to Margaret M. Booth née Cardeza, with information concerning the date of her husband, James Curtis Booth's (1810-1888), election to the Pennsylvania Horticultural Society.
Keywords: Booth, James Curtis, 1810-1888; Pennsylvania Horticultural Society; Martinez Cardeza, Margaret